Evaluation of wheat (Triticum aestivum L.) for agro-morphological and yield related traits under normal and late sowing conditions at Chitwan, Nepal - Thapa, A; Neupane, R; Srivastava, A; Panthi, B (SAARC Journal of Agriculture, 2023)
A field investigation was carried out during wheat season of 2019-2020 under normal and late sowing conditions at the research farm of the Agriculture and Forestry University, Rampur, Chitwan, Nepal to evaluate the agro-morphological and yield related traits of spring wheat. A set of thirty elite spring wheat genotypes were evaluated. The experiment was laid out in an Alpha lattice design with three replications. Each replication consisted of 30 treatments of wheat with altogether 90 treatments in three replications. Wheat was sown in two sowing dates that normal sowing date (22nd November, 2019) and late sowing date (23rd December, 2019). Significant differences were observed between two sowing dates for heading and maturity days, plant height, grains spike-1, thousand kernel weight, grain yield, biomass yield, harvest index and SPAD reading. Generally, almost all the traits manifested superiorly on normal sowing date. The mean plant height was 92.71 cm for normal and 88.3 cm for late sown condition. The mean grain yield was 2.94 t ha-1 in normal and 1.91 t ha-1 in late sown condition. Gautam had maximum grain yield that 3.84 t ha-1 followed by Bhrikuti, Vijaya and Aditya under normal sown condition. Bhrikuti had maximum grain yield (2.34 t ha-1) followed by Vijaya, Gautam and NL 297 under late sowing conditions. Significant positive correlation was found between grain yield and investigated attributes. Days to maturity, plant height, spikes per m2, grains per spike, and thousand kernel weight showed significant positive correlations with grain yield. SAARC J. Agric., 21(1): 167-174 (2023)